Managing improved water supply: Lessons from the Kerala Water Authority - Singh, Bhanwar; Ramasubban, Radhika (International Food Policy Research Institute, 1990)
If we are to find lessons in sustainable managerial improvements for irrigation by studying innovations 1 rom domestic water supply, we must begin by recognizing the similarities and dissimilarities in the two sectors (or two branches of the same sector). While water for irrigating crops and orchards concerns only one (albeit, crucial) sector of the economy and some sections of the population, water for drinking and household need:; concerns everyone. All households need water for drinking and other domestic requirements. Every household must satisfy this basic need, in varying degrees, irrespective of its occupational and income characteristics, with or without cash income. In the past, providing drinking water acquired an almost sacred character. Digging wells and cleaning, deepening, and repairing ponds to augment water ""esources for drinking and domestic needs have traditionally been a form of charity undertaken by individuals and institutions. Goverrments have also undertaken this activity mainly to relieve a famire or drought. Paying for water has never been a traditional feature of Indian villages. Rather, in procuring water, expenditure of time substituted for expenditure of money.